Pattern of Interleukin-17A and Interleukin-1β in Migraine Patients - Fardin Faraji; Ghasem Mosayebi; Afsoon Talaei; Hossein Ansari; Fatemeh Rafiei; Mobina Ravanbakhsh; Mana Shojapour (Journal of Kerman University of Medical Sciences)
Background: Migraine is a complex neurological disorder. The precise etiology of migraine is not clear. Many studies have been conducted on the association of the immune system with migraine pathophysiology. Neurogenic inflammation, the main pathomechanism of migraine, is well described. This study evaluated the pattern of changes in interleukin (IL)-1β, IL-17A, total antioxidant capacity (TAC), and malondialdehyde (MDA) in migraine patients.Methods: In this case-control study, serum samples were taken from 31 migraine patients referred to the neurology clinics of medical centers associated with Arak University of Medical Sciences. The severity of the headache was assessed with standard questionnaires. Serum samples were also obtained from 30 normal individuals. The IL-1β and IL-17A levels were measured by a sensitive ELISA method. TAC was measured by the FRAP technique, and lipid peroxidation levels were evaluated by an MDA assay. Data were analyzed descriptively and analytically using SPSS 21 software.Results: The results showed that the mean level of IL-1β in the case group was significantly higher than the control group (P = 0.01). The mean level of IL-17A was not significantly different in the two groups. The mean serum MDA level in the study group was significantly higher than in the controls (P = 0.005). No statistical difference was observed in the mean serum level of TAC between the two groups.Conclusion: According to our results, the pathogenesis of migraine can be associated with immune system function, and inhibition of pro-inflammatory cytokine production may be effective in treating migraine patients.